Ampullary Tumor Caused by Metastatic Renal Cell Carcinoma and Literature Review - haidong, wang; Jianwei, Wang; Guizhong, Li; Ning, Liu; Feng, He; Libo, Man (Urology Journal, 2014)
We present a case of a 50-year-old man with a metastasis to the ampulla of vater thatled to the discovery of renal cell carcinomas.The man was referred to us because of jaundice.Computed tomography (CT) scan of the abdomen showed irregular masses in the right kidney. Magnetic resonance imaging (MRI) revealed dilatation of the bile duct. The patient underwentright nephrectomy and pancreatoduodenectomy. Postoperative histopathologic examination revealedclear cell carcinoma in both the renal and ampullary lesions. After a 5-year follow-up ,the patient was alive with no evidence of recurrent disease.